Advances in mechanisms and challenges in clinical translation of synergistic nanomaterial-based therapies for melanoma - Zhang, Yibo; Liu, Xilin; Wu, Guangzhi (Frontiers in Cell and Developmental Biology, 2025)
Melanoma is a highly malignant form of skin cancer, with its incidence and mortality rates continuously rising on a global scale. Although traditional treatments such as surgery, chemotherapy, radiotherapy, as well as targeted and immunotherapy, have made certain progress, the efficacy of these therapeutic modalities remains limited due to the high metastatic potential, heterogeneity, and drug resistance of melanoma. In recent years, nanomaterials, with their unique physicochemical properties, have emerged as a significant research focus in tumor therapy. Nanomaterials can enhance the targeted delivery of drugs, increase drug accumulation in tumors, and reduce side effects, and they have shown great potential in the synergistic treatment of melanoma. This review summarizes the mechanistic breakthroughs of nanomaterials in the synergistic treatment of melanoma, including the combined application of nanocarriers in photothermal therapy, photodynamic therapy, and immunotherapy. It also explores how precise drug delivery can improve therapeutic efficacy and overcome tumor immune evasion and drug resistance. Furthermore, the challenges faced in the clinical translation of nanomaterial-based synergistic treatment are discussed, such as biosafety, delivery efficiency, and the need for personalized treatment. Despite these challenges, the continuous development of nanotechnology offers new hope for the comprehensive treatment of melanoma and lays the foundation for the realization of precision medicine in the future.